Superhydrophobic photothermal coatings based on candle soot for prevention of biofilm formation. (1st January 2023) - Lin, Yuancheng; Zhang, Haixin; Zou, Yi; Lu, Kunyan; Li, Luohuizi; Wu, Yan; Cheng, Jingjing; Zhang, Yanxia; Chen, Hong; Yu, Qian
Highlights: A facile method is developed for fabrication of a superhydrophobic photothermal coating based on candle soot. The coating can resist initial bacterial adhesion and kill the residual bacteria on the surface under NIR irradiation, preventing long-term biofilm formation. The coating exhibits long-term storage stability and could be deposited on diverse practical substrates. Abstract: Bacterial biofilms formed on the material surfaces have posed a series of serious problems for human health and industries. The treatment of mature biofilms is particularly difficult because they are inherently highly resistant against antibiotics and other adverse factors. The prevention is strategically advantageous over the treatment, and thus the development of innovative surfaces with capability to inhibit biofilm formation is highly demanded. In this work, we developed a superhydrophobic photothermal coating for prevention of biofilm formation, which was based on candle soot with hierarchical structure and excellent light-to-heat conversion ability. This coating was fabricated by deposition of a candle soot layer on the substrate, followed by sequential chemical vapor deposition of tetraethoxysilane and immobilization of fluorinated silane to make the coating robust and superhydrophobic. The resulted coating could repel a majority of bacteria from the surface at the early stage, and then eradicate a small number of bacteria remained on the surface under a short-term irradiation of near-infrared laser. The combination of anti-adhesive property and photothermal bactericidal property endowed the coating with good antibiofilm property to prevent biofilm formation for at least 2 weeks. This coating is facile for deposition on various substrates with good storage stability, showing great potential for diverse practical applications to solve the biofilm-associated problems of materials and devices. Graphical abstract: Image, graphical abstract